Functional gene group analysis identifies synaptic gene groups as risk factor for schizophrenia. - GILL, MICHAEL; MORRIS, DEREK; KENNY, ELAINE; CORVIN, AIDEN (My University, 2012)
Schizophrenia is a highly heritable disorder with a polygenic pattern of inheritance and a population prevalence of _1%. Previous studies have implicated synaptic dysfunction in schizophrenia. We tested the accumulated association of genetic variants in expert-curated synaptic gene groups with schizophrenia in 4673 cases and 4965 healthy controls, using functional gene group analysis. Identifying groups of genes with similar cellular function rather than genes in isolation may have clinical implications for finding additional drug targets. We found that a group of 1026 synaptic genes was significantly associated with the risk of schizophrenia (P=7.6 _ 10(-11)) and more strongly associated than 100 randomly drawn, matched control groups of genetic variants (P<0.01). Subsequent analysis of synaptic subgroups suggested that the strongest association signals are derived from three synaptic gene groups: intracellular signal transduction (P=2.0 _ 10(-4)), excitability (P=9.0 _ 10(-4)) and cell adhesion and trans-synaptic signaling (P=2.4 _ 10(-3)). These results are consistent with a role of synaptic dysfunction in schizophrenia and imply that impaired intracellular signal transduction in synapses, synaptic excitability and cell adhesion and trans-synaptic signaling play a role in the pathology of schizophrenia.
PUBLISHED
Keywords: Genetics; Neuroscience; Schizophrenia; Genes & Society; Neuroscience